In Search of True African Art from the Perspective of Relative Disciplines: Case Study of Architecture and Archaeology - Oyinloye, Michael Abiodun; Dipeolu, Adedotun Ayodele; Omolola, Feyisara Sunday; Adeyemi, Adedola Olayinka; Siyanbola, Afeez Babatunde (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
The term ‘African Art’ is typically used for the classification of the art of Sub-Saharan Africa. It appears casual, amateurish and primitive by the classical proportion of European art, which is the way traditional African art is regarded. Truth be said, the continent comprise ideas from different cultural groups and civilization, each with a unique art tradition, architecture and lifestyle. It is as a result of this, we cannot talk about African Art without reference to the impact of some related disciplines, such as architecture and archaeology. Various Studies have shown that before the advent of Europeans and Americans with their influences on Africa culture, the people have already made significant contribution to develop themselves in the areas of ancient architecture, traditional medicine and technology, the African way of life depicts so many chronologically arranged pattern of operation and such was adhered to fully and passed down from age to age. Existing scholarship addresses documented evidences of ancient civilization in the archeological records. This study traces the history of some of the African art traditions, architectural styles, belief system, foreign impact and their usefulness in the communities that produced them, vis-à-vis what they connote in the present society. Therefore, this work intends to showcase the beauty and importance of the traditional African art and architecture, and how they would enrich our knowledge of history, research as well as serve reference purpose to generations yet unborn. Keywords: African and traditional art, Architecture, Archeology, history